Chronic periodontitis can affect the levels of potential oral cancer salivary mRNA biomarkers. (23rd August 2016) - Cheng, Y.‐S. L.; Jordan, L.; Chen, H.‐S.; Kang, D.; Oxford, L.; Plemons, J.; Parks, H.; Rees, T.
Abstract : Background and Objective: More than 100 salivary constituents have been found to show levels significantly different in patients with oral squamous cell carcinoma (OSCC) from those found in healthy controls, and therefore have been suggested to be potential salivary biomarkers for OSCC detection. However, many of these potential OSCC salivary biomarkers are also involved in chronic inflammation, and whether the levels of these biomarkers could be affected by the presence of chronic periodontitis was not known. The objective of this pilot study was therefore to measure the levels of seven previously reported potential OSCC salivary mRNA biomarkers in patients with chronic periodontitis and compare them to levels found in patients with OSCC and healthy controls. The seven salivary mRNAs were interleukin (IL)‐8, IL‐1β, dual specificity phosphatase 1, H3 histone family 3A, ornithine decarboxylase antizyme 1, S100 calcium‐binding protein P (S100P) and spermidine/spermine N1‐acetyltransferase 1. Material and Methods: Unstimulated whole saliva samples were collected from a total of 105 human subjects from the following four study groups: OSCC; CPNS (chronic periodontitis, moderate to severe degree, non‐smokers); CPS (chronic periodontitis, moderate to severe degree, smokers); and healthy controls. Levels of each mRNA in patient groups (OSCC or chronic periodontitis) relative to the healthy controls were determined by a pre‐amplification reverse transcription–quantitative polymerase chain reaction approach with nested gene‐specific primers. Results were recorded and analyzed by the Bio‐Rad CFX96 Real‐Time System. Mean fold changes between each pair of patient vs. control groups were analyzed by the Mann–Whitney U ‐test with Bonferroni corrections. Results: Only S100P showed significantly higher levels in patients with OSCC compared to both patients with CPNS ( p = 0.003) and CPS ( p = 0.007). The difference in S100P levels between patients with OSCC and healthy controls was also marginally significant ( p = 0.009). There was no significant difference in the levels of salivary IL‐8, IL‐1β and dual specificity phosphatase 1 mRNAs between patients with OSCC and patients with CPNS ( p = 0.510, 0.058 and 0.078, respectively); no significant difference in levels of salivary ornithine decarboxylase antizyme 1 and spermine N1‐acetyltransferase mRNAs between patients with OSCC and patients with CPS ( p = 0.318 and 0.764, respectively); and no significant difference in levels of the H3 histone family 3A mRNA between patients with OSCC and either CPS ( p = 0.449) or healthy controls ( p = 0.107). Conclusions: Salivary S100P mRNA could be a reliable biomarker for OSCC detection, regardless of the presence of chronic periodontitis. The presence of chronic periodontitis could significantly affect the levels of the other six mRNAs, and negatively influence reliability for using them as biomarkers for oral cancer detection.